2008
DOI: 10.1179/joc.2008.20.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rifampicin and Moxifloxacin Efficacy in an Experimental Model of Animal Brucellosis

Abstract: Brucellosis is an important health issue in many parts of the world and clinicians are still seeking for better treatment choices. The aim of this study was to investigate the efficacy of moxifloxacin in an experimental brucellosis model and to compare its activity with rifampicin. Wistar albino rats infected with Brucella abortus were then randomized into 3 groups, which received rifampicin, moxifloxacin, and tap water, respectively. After 21 days, they were sacrificed and spleen, liver and blood cultures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…To assess the effects of antibiotic treatment to halt Brucellainduced arthritis, mice with established inflammation were treated with rifampicin, which is effective at treating experimental models of brucellosis [45,46] and is used in conjunction with doxycycline for treatment of brucellosis in humans [9]. Rifampicin alone was effective at clearing infection, treating systemic symptoms of disease (weight loss/ruffling of the fur, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the effects of antibiotic treatment to halt Brucellainduced arthritis, mice with established inflammation were treated with rifampicin, which is effective at treating experimental models of brucellosis [45,46] and is used in conjunction with doxycycline for treatment of brucellosis in humans [9]. Rifampicin alone was effective at clearing infection, treating systemic symptoms of disease (weight loss/ruffling of the fur, etc.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the efficacy of antibiotics to treat focal inflammation as a result of experimental brucellosis, IFN-␥ Ϫ/Ϫ mice (BALB/c background) were nasally infected with B. melitensis 16M and treated orally with rifampicin, starting 5 weeks after infection. Rifampicin was selected, as it can successfully treat experimental brucellosis [45,46] and is commonly used in combination with doxycycline to treat human brucellosis [47,48]. Doxycycline was not used in conjunction with rifampicin in this study, as it causes diarrhea and weight loss in mice [49].…”
Section: Oral Antibiotics Halt Development Of Brucella-induced Paw Inmentioning
confidence: 99%
“…Rats chronically treated with ethanol have an increased susceptibility to B. melitensis due to a decrease in protective cellular immunity [72]. The rat model has also been used to study the efficacy of various antibiotics for treating Brucella infection [7476]. Sprague Dawley rats were used to evaluate the efficacy of spiramycin, a macrolide antibiotic, for treating brucellosis, since this drug has no teratogenic effect, and therefore it is safe for pregnant women [74].…”
Section: Other Laboratory Animal Models For Brucellosismentioning
confidence: 99%
“…However, the likely efficacy of these antibiotics in vivo is unclear. The only known report of moxifloxacin evaluation in a rat model of brucellosis indicated that it may be an alternative choice for antibiotic treatment of brucellosis [6]. There is no known evaluation of gatifloxacin treatment of brucellosis in vivo.…”
Section: Introductionmentioning
confidence: 98%